P-519 Relationship between the quality control parameters in PGT-A results by NGS with the chromosomal mosaicism diagnosis in trophoectoderm biopsies. (30th June 2022) - Morales Sabater, R; Lledo, B; Ortiz, J.A; Cascales, A; Ten, J; Bernabeu, A; Bernabeu, R
Abstract: Study question: Are quality control (QC) parameters in NGS results related to mosaicism rate in trophoectoderm samples? Summary answer: A high number of filtered reads in PGT-A results correlates with a higher mosaicism rate. But the overall noise does not influence the mosaicism rate. What is known already: The implementation of NGS have led to increased reporting of mosaicism. There is intense research on the biological mechanisms behind mosaicism, but also on the technical factors that might be influencing in its diagnosis. Low quality samples and DNA amplification artefacts lead to an increase in overall noise after sample analysis. The Derivative Log Ratio (DLR) quality control parameter in sequencing results measures the overall noise present in a sample. High DLR values indicate noisy profiles. Additionally, insufficient numbers of sequencing reads will result in noisy profiles and false copy number assignments. Study design, size, duration: A retrospective analysis of PGT-A results, corresponding to trophoectoderm biopsies from embryos on day 5, 6 or 7 of development, was performed (February 2017- November 2021). After the quality analysis, 5245 samples that reached the optimum QC measures were included (samples with DLR < 0.4 and number of filtered reads > 250.000). Participants/materials, setting, methods: PGT-A was carried out with the VeriSeq kit (Illumina), after genome amplification with the Picoplex technique. Sequencing data was analyzed with BlueFuse Multi software (Illumina). Data analysis was performed using SPSSv20.0. An embryo was designated as mosaic when the percentage of aneuploidy for at least one chromosome was between 25 and 50%. For this study, we considered euploid-aneuploid and aneuploid-aneuploid mosaic embryos. Main results and the role of chance: Considering the 5245 samples included in the analysis, the number of embryos carrying chromosomal mosaicism was 960, which corresponds to 18.3%. To analyze whether the percentage of mosaic embryos varied according to the DRL, we used a logistic regression analysis, introducing maternal and paternal age, embryo quality, and biopsy day as confounding variables, and categorized the DLR using as a point cut the median (0.19). There were no significant differences in the percentage of embryos carrying mosaicism between the group of higher DLR (≥0.19) compared to the group of lower DLR (<0.19) (18.7% vs 18.0%; p = 0.278). On the other hand, to study the relationship between mosaicism and the number of filtered reads obtained in the sequencing analysis, we performed the same analysis using the median of filtered reads (556.688) as cut point. The samples with a number of filtered reads higher than the median had a higher rate of mosaicism (19.3% vs 17.4%, p = 0.041). Moreover, we analyse the data according to the type of mosaicism (segmental or whole chromosome) and we did not observe any difference neither for the DLR nor for the reads. Limitations, reasons for caution: The main limitation of this study compared with other studies is the different criteria in the mosaicism diagnosis between the different laboratories. Moreover, we are not able to identify if worse QC are due to issues with the biopsy procedure, sample quality, DNA amplification or library preparation. Wider implications of the findings: The overall noise in PGT-A results doesn't seem to influence the mosaicism rate. However, increased mosaicism rate is observed in samples with high number of filtered reads. This finding suggests that too many cells may lead to amplification saturation and underestimation of the relative quantity of DNA. Trial registration number: Not applicable